KARAKTERISTIK SIFAT MEKANIK DAN STRUKTUR MIKRO VALVE (KATUP) SEPEDA MOTOR RODA DUA TIPE ORI DAN TIPE KW - Sutrisno Sutrisno; Taufiq Hidayat (Journal of Mechanical Engineering, 2018)
Valve is one of the components contained in the two-wheeled vehicles and four wheels. The valve acts as a regulator for the exit of fuel and air into the combustion chamber. In four stroke cycle combustion there is no two types of valves ie suction valve and exhaust valve. the auto parts store sells motorcycle spare parts we know the type of original valve and KW type. The ori valve is the original valve of the motorcycle from motorcycle manufacturer, while the KW valve is a production valve not from a motorcycle manufacturer. This research is used to analyze hardness characteristic and micro structure from ori valve type and KW valve type.The test method used is chemical composition test, Vickers hardness test and micrography. KW valve types have a grain structure of more orbiting chromatic carbides dominating and spread more evenly in all areas, thus affecting significant increases in hardness compared to ori valve types. There is bainite in small quantities. The hardness number of the valve stem is 206,0 VHN. The hardness number of the head valve is 329 VHN. The original motorcycle valve has a granular structure of chromium carbide is small amount and not evenly dispersed. Domination on the bainite structure, so that the hardness of the original type valve is lower than that of the valve with KW type. The hardness number on the valve stem is 182.5 VHN and the valve head is 251.3 VHNKeywords: valve, Vickers, original , KW